Perencanaan Reservoir Berdasarkan Jumlah Kebutuhan Air di Desa Semidang Alas Kelurahan Jokoh Kota Pagaralam - Perniko sandi; Alharia Dinata (JURNAL ILMIAH BERING'S, 2016)
Water is the most important component for life. All living beings on the planet definitely needs water for its survival water supply is sufficient and controlled in an environment in which we live, is an important thing that must be met (Mays, 2001). The water supply system in the village of Alas Semidang kel. Jokoh district. Central Dempo Pagaralam using a network of gravity-fed piping for the water source higher than the village. In this study discussed about the dimensions of the reservoir based on the amount of water needs in rural villages Semidang pedestal jokoh Pagaralam, which Planning dimensions of the reservoir in the village of Alas Village Semidang Jokoh Pagaralam planned for the next 10 years. From the data and the results of calculating the dimensions of the reservoir in the village Semidang Alas Village Jokoh Pagaralam for 10 years in the can dimensions reservoir: Length (p) = 1 m, width (l) = 2 m, Height (t) = 2 m, height surveillance (Fb) = 0.5 m. So Reservoir Dimensions: 1 m x 2 m x 2.5 m.